Multigrid methods for saddle point problems: Oseen system. (1st November 2017) - Brenner, Susanne C.; Li, Hengguang; Sung, Li-yeng
Abstract: We develop and analyze multigrid methods for the Oseen system in fluid flow. We show that the W -cycle algorithm is a uniform contraction if the number of smoothing steps is sufficiently large. Numerical results that illustrate the performance of the methods are also presented.